Islamic Jurisprudence in Addressing Child Abuse and Domestic Violence - Adinda Suhaibah; Arjan Saputra Harahap; Rahmad Nasution; Jalaluddin Al Mahalili Hamzah; Ali Imran Sinaga (Hikmah, 2026)
This study aims to analyze the perspective of Islamic jurisprudence on addressing child abuse and domestic violence, as well as to examine its relevance to child protection regulations in Indonesia. The study employs a descriptive qualitative method using a literature review and a normative legal approach. Primary data sources include the Qur’an, hadith, Islamic jurisprudence provisions, Law No. 35 of 2014 on Child Protection, and Law No. 23 of 2004 on the Elimination of Domestic Violence. Secondary data were obtained from books, scientific articles, and various literature related to child abuse, family relations, and legal protection from both an Islamic and positive law perspective. Data analysis was conducted using content analysis techniques to identify and interpret the concepts of violence, child protection, family responsibility, and the principle of justice in Islamic jurisprudence. The research results indicate that Islamic jurisprudence rejects all forms of violence that harm the soul, dignity, and honor of human beings. Islam views children as a trust that must be protected, while the family must be built on the foundations of love, justice, consultation, and shared responsibility.